Analysis of the Trickle-Down Effect and Multiplier Effect of Religious Tourism at Al-Jabbar Mosque: How does it impact local MSME? - Sutisna, Fajar Andrian; Sopiah, Evi; Salam, Annisa Nur (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This research aims to analyze the trickle-down and multiplier effects of the Al-Jabbar Mosque as a religious tourism site using a qualitative approach and descriptive analysis method using NVivo software. Primary data was collected through interviews with 20 tourists, 10 local MSME actors, 5 MSME employees, also the food court manager, and Al-Jabbar Mosque management. The findings reveal that the presence of Al-Jabbar Mosque generates a trickle-down effect by creating business potential and job opportunities for the local community. Local Community can engage in trade within the food court, also benefit from special programs like rental fee discounts. Additionally, there are employment opportunities at the mosque, such as security. The mosque also opens opportunities for MSME employment and open service, such as photography. Currently, 70% of the 550 mosque employees are local residents. Tourist visits directly impact Rp144.648.000.000 monthly to local MSME income, assuming 344,941 visitors per month with an average expenditure of Rp344,833 on food, photography, and other services. Mathematical analysis shows a multiplier effect value of 1.22, indicating that for every Rp100,000 increase in tourist spending, local MSME income rises by Rp122,000. Practically, the research suggests that Al-Jabbar Mosque management should collaborate with the local community to develop new businesses.